2020
DOI: 10.21203/rs.2.15803/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motivations, experiences and aspirations of Trainee Nursing Associates in England. A qualitative study

Abstract: Background The nursing associate role was developed in England in response to the ‘Shape of Caring’ review. It has been implemented to fulfil two aims; to bridge the gap between registered nurses and healthcare assistants, and to provide an alternative route into registered nursing in light of workforce shortages. Other high income countries deploy second level nurses within their healthcare systems, however the UK has a turbulent history with such roles. The previous state enrolled nurse was phased out in the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…The literature identified through this review links the over-representation of ME workers in low paid jobs, including health and social care, to historical segmentation and selection practice into specific sectors and occupations (Hudson et al, 2017). Furthermore, income reliance due to socio-economic disadvantages and having families and caring responsibilities act as push factors to accept low-paid, local jobs in social care among minority ethnic workers (King et al, 2020). These 'sorting' processes of particular groups into lower-paid occupations exacerbate racialised and gendered stereotypes of caring jobs, particularly those involving domiciliary and live-in care (Atkinson and Crozier, 2020;Farris, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature identified through this review links the over-representation of ME workers in low paid jobs, including health and social care, to historical segmentation and selection practice into specific sectors and occupations (Hudson et al, 2017). Furthermore, income reliance due to socio-economic disadvantages and having families and caring responsibilities act as push factors to accept low-paid, local jobs in social care among minority ethnic workers (King et al, 2020). These 'sorting' processes of particular groups into lower-paid occupations exacerbate racialised and gendered stereotypes of caring jobs, particularly those involving domiciliary and live-in care (Atkinson and Crozier, 2020;Farris, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These and other interventions call for organisational level changes, such as introducing procedures to raise awareness of bullying and provide a bullying reporting mechanism, as well as individual-level interventions such as the provision of training and education to change behaviours or perceptions in a way that ensures responsibilities are placed on the perpetrators of bullying rather than the victims (Gillen et al, 2017). Support structures also need to be put in place, such as creating 'communities of practice' (King et al, 2020) and 'safe spaces' (Ross et al, 2020) to facilitate career progression and empower workers' voices.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous work has shown that during the development and implementation of this new, second level, nursing associate qualification, students and staff often feel in a liminal space with role and task boundaries often being unclear (Davey, 2019; King et al., 2020). Findings here suggest that COVID‐19 accentuated this.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in patient contact, discontinuation of clinical placements, reduced supervision and redeployment were all reported. TNAs already face challenges in their training relating to clinical support and career development opportunities (King et al., 2020) and in relation to “worker” versus “learner” perceptions (Coghill, 2018). These have been compounded by COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Initial research into nursing associate trainees' experiences largely focused on the training model. In these studies, role ambiguity and the need for role clarity (Coghill, 2018) (King et al, 2019), as well as the need for education and communication about the scope of practice of the role has been reported (Health Education England, 2019). An evaluation of the nursing associate role including expert interviews, a survey with chief nurses in England and case studies of two NHS organisations providing community and mental health care has also been conducted (Kessler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%